(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
That any industrial company that must think about marketing mechanisms and who are the beneficiaries and the pursuit of gain customer satisfaction with access to competitive advantages. Most industrialized our companies from a variety of problems experienced both in the field of production, marketing, or keep up with new developments or commitment to quality standards, which caused the reluctance of customers to buy local products for various reasons, and especially in light of unplanned economic policy and exposure to market to imported products flooding the market with various goods and services that do not can the domestic industry rival, which has competitive advantages and meet business requirements, but others arrived to stop or as well as the General Company for batteries firmly established companies face many challenges this study seeks to analytical identify strengths and weaknesses and their causes from both institutional matter and customers. And find realistic solutions which contribute to the upgrading of local products and the strengthening of the national economy